Navigating complexity: A case study of triple primary cancers in breast, lung, and rectum - Chakrabarti, Jayanta; Adak, Arnab; Nanda, Durgaprasad; Maity, Namrata (Indian Journal of Case Reports, 2025)
The advancement of technology in tumor identification and therapy has led to a significant rise in the prevalence of multiple primary malignant tumors. Triple or more primary malignancies are rare and their management poses a major challenge. For optimum outcomes, a multidisciplinary strategy and customized decision-making for each patient are helpful. Here, we present a case of a 47-year-old female with triple primary malignancies of breast, rectum, and lung. To the best of our knowledge, this is the first review of a breast carcinoma that was metachronous to both lung and rectum in which lung and rectum carcinomas developed synchronously.